Synthesis, crystal structure, and ADME prediction studies of novel imidazopyrimidines as antibacterial and cytotoxic agents - Senge, Mathias (Wiley, 2020)
In the present study, a novel series of polyfunctionalized imidazopyrimidines 6a–u and 9a–d were efficiently constructed by a domino reaction between 2‐imino‐6‐substituted‐2,3‐dihydropyrimidin‐4(1H)‐ones 4a–d or 8a–c and 2‐bromoacetophenones 5a–i under mild basic conditions. The synthesized series were screened for their antibacterial activity against Staphylococcus aureus and Bacillus subtilis as Gram‐positive (+) bacteria, as well as against Gram‐negative (−) bacteria Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella typhi. Most of the synthesized derivatives of imidazopyrimidines 6 and 9 showed remarkable selectivity against Gram(−) bacteria over the Gram(+) ones. Compounds 6c, 6f, and 6g displayed potent and broad‐spectrum antibacterial activity against all tested strains. Compounds 6f and 6g displayed promising inhibitory activity on GryB ATPase from E. coli with IC50 = 1.14 and 0.73 μM, respectively. Simultaneously, some of the synthesized imidazopyrimidines were screened for their antiproliferative activity against 60 cancer cell lines at a concentration of 10 μM. Compound 9d showed potent activity against most of the tested cell lines, with a mean growth inhibition of 37%. The ADME (absorption, distribution, metabolism, and excretion) prediction study demonstrated that the synthesized hits have, in addition to their promising chemotherapeutic activity, acceptable pharmacokinetic properties, and a drug‐likeness nature to be further developed.
Keywords: ADME; Antibacterial activity; Antiproliferative activity; Imidazopyrimidine